PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, DAN UKURAN DEWAN KOMISARIS TERHADAP AGRESIVITAS PAJAK PERUSAHAAN (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021) - Rivan Afdhal; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of institutional ownership, managerial ownership, and the size of the board of commissioners on corporate tax aggressiveness. This study uses tax aggressiveness as the dependent variable and institutional ownership, managerial ownership, and the size of the board of commissioners as independent variables.            This study applies regression analysis of panel data using a sample of mining companies listed on the Indonesia Stock Exchange for the period 2018 to 2021. By using purposive sampling in sample selection, 92 research samples were obtained for four consecutive years (2018-2021).            Using a sample of companies listed on the Indonesia Stock Exchange, empirical evidence, of mining companies listed between 2018 and 2021, this empirical research shows that institutional ownership has a significant and negative effect on corporate tax aggressiveness. Meanwhile, managerial ownership and the size of the board of commissioners do not have a significant relationship to corporate tax aggressiveness.